Pengaruh Literasi Keuangan, Kemampuan Manajerial Dan Peran Financial Technology (Fintech) Payment Terhadap Kinerja UMKM - Chita Sari, Dewi; Suyanto, Suyanto; Kurniawan, Angga (Universitas Muhammadiyah Metro, 2024)
This study aims to determine the Effect of Financial Literacy, Managerial Ability and the Role of Financial Technology (fintech) Payment on the Performance of Culinary MSMEs in Metro City. The type of research used in this study is quantitative. This study uses primary data through questionnaires, and the population used in this study amounted to 1080. The sampling technique in this study was reduced by using purposive sampling according to the characteristics determined by the researcher; the sample taken in this study was 100 respondents. The result of this study indicat that financial Literacy Influences the performance of culinary MSMEs, Managerial Skills affect performance of culinary MSMEs, and the role of financial technology (fintech) payment affect performance of culinary MSMEs Taken Together the variable. The results of this study indicate that financial literacy, managerial ability, and the role of financial technology (fintech) payment affect the performance of culinary MSMEs in Metro City